Profile of Physical Conditions of Metropolis FC Soccer Athletes: Profil Kondisi Fisik Atlet Sepakbola Metropolis FC - Ori Alfarizi; M. Fransazeli (Badnur Medisa Group, 2023)
Football is a sport that is most in demand by all groups, both from children, adolescents, adults to the elderly who always popularize this sport. Good and prime physical condition and ready to face opponents are important elements in the game of football. Physical conditions that are needed in the sport of football include endurance, explosive power, speed and agility. This study aims to find out how well the Physical Condition Profile of Metropolis Fc Football Athletes. This type of research is descriptive research. The subjects of this study were football athletes from Metropolis FC with a total of 20 subjects. Data collection using test measurements. The test instruments used were aerobic endurance (balke test), arm muscle endurance (60 seconds push-up test), speed (30 meters running test), agility (Illinois test), leg and back dynamometer, explosive power (standing long jump). ) and coordination (throw catch baseball). The analysis technique carried out is pouring the frequency into the form of a percentage. The results showed that the profile of the physical condition of Metropolis Fc athletes was that there were 3 people or 15% categorized as very good, 1 person or 5% categorized as good, 6 people or 30% categorized as moderate, 6 people or 30% categorized as poor and 4 people or 20% categorized as less.